2013
DOI: 10.1080/17461391.2013.832803
|View full text |Cite
|
Sign up to set email alerts
|

Endurance athletes' coping function use during competitive suffering episodes

Abstract: Endurance athletes who realise that they are falling short of important personal goals during competition are expected to experience competitive suffering. As a negative affective state with implications for performance and personal experiences, it is important to understand how endurance athletes cope with competitive suffering. Thus, the purpose of this study was to investigate differences in athletes' momentary coping function use over time during a competitive suffering episode. Twenty-six runners (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Second, the gestalt of enduring general fatigue and experiencing difficult situations refers to the difficulties (e.g., health problems, injuries, lack of preparation, or challenging environmental settings) that runners must cope with; it is the experience of surmounting these difficulties with emotional, cognitive, or behavioral strategies, as suggested by research on coping in endurance sports (Evans et al, 2014). Interestingly, Atkinson (2008, 2015) highlighted how triathletes and fell runners come together as a “pain community” and share physical and mental suffering in the sport through a collective quest and self-exploration, which suggests that this typical experience of suffering is embedded in the culture of practice in ultra-endurance sports.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the gestalt of enduring general fatigue and experiencing difficult situations refers to the difficulties (e.g., health problems, injuries, lack of preparation, or challenging environmental settings) that runners must cope with; it is the experience of surmounting these difficulties with emotional, cognitive, or behavioral strategies, as suggested by research on coping in endurance sports (Evans et al, 2014). Interestingly, Atkinson (2008, 2015) highlighted how triathletes and fell runners come together as a “pain community” and share physical and mental suffering in the sport through a collective quest and self-exploration, which suggests that this typical experience of suffering is embedded in the culture of practice in ultra-endurance sports.…”
Section: Discussionmentioning
confidence: 99%
“…A PRISMA flow diagram illustrating the sequence of dataset selection is depicted in Figure 1. The final pool included 18 independent studies (Haney and Long, 1995; Smith and Christensen, 1995; Amiot et al, 2004; Gaudreau and Blondin, 2004b; Hatzigeorgiadis, 2006; Gaudreau and Antl, 2008; Van Yperen, 2009; Gaudreau et al, 2010; Levy et al, 2011; Nicolas et al, 2011; Nicholls et al, 2012a,b; Schellenberg et al, 2013; Doron and Gaudreau, 2014; Evans et al, 2014; Laborde et al, 2014a,b). A variety of questionnaires, which classified coping in many different ways, were reported in the primary investigations.…”
Section: Methodsmentioning
confidence: 99%
“…Measures used to assess goal attainment include the 12-item Attainment of Sport Achievement Goal Scale (Gaudreau and Amiot, manuscript submitted), a 3-item scale (Gaudreau et al, 2010), a 2-item scale (Gaudreau and Blondin), or a sliding scale anchored at −5 (negative feeling about ability to achieve goal) and +5 (positive feelings about ability to achieve goal; Evans et al, 2014). The majority of these studies (e.g., Amiot et al, 2004; Gaudreau and Antl, 2008; Nicolas et al, 2011; Schellenberg et al, 2013) found a positive association between goal attainment and task oriented coping, but a negative relationship between goal attainment and disengagement-oriented coping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Daily coping inventory, people are asked the same day the stressful situation. Recent studies develop and implement methods that would minimize the retrospective bias (Calmeiro & Tenenbaum, 2007;Calmeiro, Tenenbaum, & Eccles, 2010Doron & Gaudreau, 2014;Evans, Hoar, Gebotys, & Marchesin, 2014;Gaudreau et al, 2010).…”
mentioning
confidence: 99%